Focus on mammals - Parker, Jane (Gloucester London, 1988)
This series explores the wide range of popular science topics from many different viewpoints. Science, history, maths, geography, technology, language, art and music are some of the many aspects treated in the cross-curricular approach. The information is reinforced by imaginative projects.